Generalized Anxiety Disorder 7-Item (GAD-7) Scores in Medically Authorized Cannabis Patients—Ontario and Alberta, Canada. (June 2022) - Lee, Cerina; Round, Jessica M.; Hanlon, John G.; Hyshka, Elaine; Dyck, Jason R.B.; Eurich, Dean T.
Objectives: Despite increasing rates of legalization of medical cannabis worldwide, the current evidence available on its effect on mental health outcomes including anxiety is of mixed results. This study assesses the effect of medical cannabis on generalized anxiety disorder 7-item (GAD-7) scores in adult patients between 2014 and 2019 in Ontario and Alberta, Canada. Methods: An observational cohort study of adults authorized to use medical cannabis. The GAD-7 was administered at the time of the first visit to the clinic and subsequently over the follow-up time period of up to 3.2 years. Overall changes in GAD-7 scores were computed (mean change) and categorized as: no change (<1 point); improvement; or worsening—over time. Results: A total of 37, 303 patients had initial GAD-7 scores recorded and 5, 075 (13.6%) patients had subsequent GAD-7 follow-up scores. The average age was 54.2 years (SD 15.7 years), 46.0% were male, and 45.6% noted anxiety symptoms at the baseline. Average GAD-7 scores were 9.11 (SD 6.6) at the baseline and after an average of 282 days of follow-up (SD 264) the average final GAD-7 score recorded was 9.04 (SD 6.6): mean change −0.23 (95% CI, −0.28 to −0.17, t [5, 074]: −8.19, p -value <0.001). A total of 4, 607 patients (90.8%) had no change in GAD-7 score from their initial to final follow-up, 188 (3.7%) had a clinically significant decrease, and 64 (1.3%) noted a clinically significant increase in their GAD-7 scores. Conclusions: Overall, there was a statistically significant decrease in GAD-7 scores over time (in particular, in the 6–12-month period). However, this change did not meet the threshold to be considered clinically significant. Thus, we did not detect clinical improvements or detriment in GAD-7 scores in medically authorized cannabis patients. However, future well-controlled clinical trials are needed to fully examine risks or benefits associated with using medical cannabis to treat anxiety conditions.